Formation of Host-guest Complexes of Amino Acids and Cucurbit[7]uril - CONG, HANG; TAO, LONG-LING; YU, YI-HUA; YANG, FAN; DU, YING; TAO, ZHU; XUE, SAI-FENG (Asian Journal of Chemistry, 2010)
Interaction of amino acid hydrochlorides (guests) by cucurbit[7]uril (Q7, host) has been studied by 1H NMR. UV-vis spectra titration are employed in present study and the interaction models of 1:1 between guests and host is obtained. The binding constants (Ka) of TryHCl, PheHCl and TyrHCl for Q7 are 3.73 × 105, 8.15 × 105, and 2.33 × 105 L/mol, respectively.